ANALISIS RASIO KINERJA KEUANGAN PEMERINTAH KABUPATEN SIDOARJO BERDASARKAN LAPORAN REALISASI ANGGARAN TAHUN 2019-2022 - Yanuar Setio Wicaksono; Eni Duwita Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The conduct of this study intends to find out the financial performance of the Kabupaten Sidoarjo Government by using the Government Financial Statements in the form of the 2019-2022 Budget Realization Report which serves as the main data. Quantitative descriptive methods are used for the research carried out. To find out the financial performance of the Sidoarjo Regency Government, it is calculated using various ratios, including based on regional independence, regional financial dependence, and degree of decentralization. growth, efficiency, and effectiveness. The results obtained from this study found that the value of Sidoarjo Regional Independence during 2019-2022 was on a scale of 60% - 80% so that it was still considered not fully independent. The Regional Financial Dependency Ratio (RKKD) of Sidoarjo has an interval scale of 50% - 60% and shows that it is still very dependent on transfer receipts. The Degree of Decentralization Ratio (RDD) of Sidoarjo Regency is on an interval scale of 30% - 50% which means that it has the ability to run regional autonomy independently. The growth ratio shows an interval scale of 0% - 25% which means that the Sidoarjo Regency Government is still unable to increase its revenue and manage its finances. The value of government revenue effectiveness shows its effectiveness with more than 100%. Meanwhile, the weight of the Sidoarjo Regency Government's revenue efficiency is more than 100%, which shows that the cost of collecting PAD is greater than the realization of PAD.